THE FEASIBILITY OF MICRO-CRYOGENIC TECHNOLOGY APPLICATION FOR ENHANCING DOMESTIC NATURAL GAS UTILIZATION, CASE STUDY : NATURAL GAS PROVISION AT R & D CENTRE FOR OIL AND GAS TECHNOLOGY "LEMIGAS" - Yusep K Caryana (Scientific Contributions Oil and Gas, 2000)
Indonesia with a huge natural gas reserves distributed in various islands and separated by sea has utilized the gas for domestic energy source and petrochemical feedstock purposes. Transportation of the gas to its consumers can be in the form of either pipeline gas or Liquefied Natural Gas (LNG) schemes. Selection of the scheme chosen is determined based on its economic evaluation and technical reliability. The distribution of gas reserves in various islands segmented by sea in Indonesia in combination with economic activity concentration especially in Java island bring about difficulties in gas development due to the up-front massive investment required on gas pipe laying or LNG plant construction. It is therefore required to find a cheaper alternative to the scheme with an established safety standard application, in order that the domestic gas utilization will be able to be enhanced and thus reducing petroleum liquid import. An alternative that can be significantly considered is micro-cryogenic technology development in Indonesia for constructing a low capacity LNG plant so that a small scule of LNG can be economically produced. The LNG is then distributed to gas consumers at regions which has no existing and will not be viable for new gas network installation. Micro-cryogenic technology application is thought to be developed considering a preliminary feasibility study results. The study found that micro-cryogenic technology is around US$ 0,75 million (68,2%) cheaper than gas pipeline technology to provide natural gas for Gas Demonstration Plant operation at R& D Centre for Oil and Gas Technology "Lemigas"